Selective Growth and In Situ Transfer of Graphene on GaN Using Patterned SiO2 Supporting Layers. (17th September 2015) - Kwon, Hye-Jin; Kang, Jang-Won; Hong, Sang-Hyun; Kim, Na-Yeong; Park, Seong-Ju
Abstract : We report the selective growth and in-situ transfer of graphene on a gallium nitride layer in solution using patterned SiO2 supporting layers. The line-patterned multilayer graphene was selectively transferred onto a gallium nitride target substrate without producing the damage and defect in the graphene. Furthermore, the transfer yield of in-situ transferred graphene was greatly increased compared to that by the conventional transfer method and the adhesion of transferred graphene was also improved by in-situ transfer in solution.